2003
DOI: 10.2134/jeq2003.1258
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Triticonazole Dissipation after Seed or Soil Treatment

Abstract: This study examined the long-term fate of the fungicide triticonazole (TTZ; 5-[(4-chlorophenyl)methylene]-2,2-dimethyl-1-(1H-1,2,4-triazol-1-ylmethyl)cydopentanol) applied at a normal field dose (8.9 g ha(-1)) via seed treatment, which is the normal alternative in practice. The TTZ was applied to wheat (Triticum aestivum L.) grains as a disinfectant before sowing or spraying on bare soil for comparison and reference to the seed treatment. The seeds were germinated and grown in pots in a greenhouse at 22 +/- 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…In our comparisons of FLC susceptibility among C. neoformans genotypes, we targeted veterinary isolates where prior exposure to antifungal agents was very unlikely. However, we cannot completely rule out prior exposure to all azoles, as azole-based formulations are used in many countries, including Australia, to protect crops from pathogenic fungi and as wood preservatives (2,16,28). Studies have shown that some environmental fungi of clinical importance can develop cross-resistance to medical azoles following exposure to agricultural azoles (34,39,46).…”
Section: Vol 48 2010 Antifungal Susceptibility In Cryptococcus Genomentioning
confidence: 99%
“…In our comparisons of FLC susceptibility among C. neoformans genotypes, we targeted veterinary isolates where prior exposure to antifungal agents was very unlikely. However, we cannot completely rule out prior exposure to all azoles, as azole-based formulations are used in many countries, including Australia, to protect crops from pathogenic fungi and as wood preservatives (2,16,28). Studies have shown that some environmental fungi of clinical importance can develop cross-resistance to medical azoles following exposure to agricultural azoles (34,39,46).…”
Section: Vol 48 2010 Antifungal Susceptibility In Cryptococcus Genomentioning
confidence: 99%
“…TRZ is a chiral fungicide with one asymmetrically substituted C atom, consisting of two enantiomers, S -triticonazole and R -triticonazole (Figure S1). It is mostly used as a racemate for grains, soybeans, vegetables, and various fruits and can be used as a seed disinfectant to prevent seed-borne diseases . It has been reported that the degradation of the two enantiomers was enantioselective.…”
Section: Introductionmentioning
confidence: 99%
“…It is mostly used as a racemate for grains, soybeans, vegetables, and various fruits and can be used as a seed disinfectant to prevent seed-borne diseases. 12 It has been reported that the degradation of the two enantiomers was enantioselective. S-TRZ was more persistent than R-TRZ in fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticide-treated seeds are increasingly being formulated as a chemical application method for reducing environmental exposure (Agarwal and Sinclair, 1997;Maloy, 1993;Dawson, 1987;Bateman et al, 1986), but early studies only considered atmospheric movement, personal exposure during handling, or dissipation in the soil profile (Börjesson et al, 2003;Waite et al, 2001;Gray et al, 1983). Poag et al (2005) recently demonstrated the economic feasibility of fungicide seed treatment, suggesting that the insignificant input for seed treatment results in significant enhanced profitability.…”
mentioning
confidence: 99%
“…Many of the pesticides being used for seed treatment exhibit time-dependent sorption (Börjesson et al, 2003). According to Brusseau (1998), the importance of nonlinear sorption is dependent on the degree of spreading, and ratelimited sorption is dependent on the magnitude of characteristic reaction time to contaminant residence time.…”
mentioning
confidence: 99%